Implementation of the PsoWell™ Model for the Management of People with Complex Psoriasis - Rachael M. Hewitt; Rachael Pattinson; Lis Cordingley; Christopher E.M. Griffiths; Elise Kleyn; Helen McAteer; Julia Schofield; Chris Bundy (Medical Journals Sweden, 2021)
The Psoriasis and Well-being (PsoWell)™ training programme, incorporating motivational interviewing, improves clinicians' knowledge and skills to manage complex psoriasis, including behaviour change. The aims of this study were to deliver the PsoWell™ training programme to dermatology specialists, and to evaluate the acceptability and feasibility of implementing the PsoWell™ model across dermatology services. Framework analysis of 19 qualitative semi-structured interviews was performed, following delivery of nine, 1-day PsoWell™ training days involving 119 participants. Two themes were identified: "Perceptions and Priorities" and "Awareness", sub-divided into: "Awareness Not Competence" and "Increasing Awareness". The PsoWell™ model was found to be acceptable and feasible to implement across dermatology settings. Participants were more skilled and motivated to address psychological issues, including behaviour change, but wanted further training to ensure competency. The trainees claimed that scepticism among some colleagues regarding whole-patient management might prevent uptake. Data showing the impact on health outcomes are needed and might overcome scepticism. Remote consultation could adopt the PsoWell™ approach.